Vous êtes sur la page 1sur 4

h( x) = 0

f ( x)

f

h

n f

f(x 1 ,

S = { x Ω : h( x) = 0}

:

x = (x 1 ,

, x n ) R n

0

, x n ) R

x = (x 1 ,

, x n ) R n

h( x) =

h :

h( x) = h 1 ( x),

,

h p ( x)

R p 1 p n C 2

h

, Dh p ( x)

x S Dh 1 ( x),

R n

S x S p

T x

S = (Dh 1 ( x),

, Dh p ( x)) .

S x R n n p

T x

S = {

v R n : i = 1,

, p, v, Dh i ( x) = 0}.

p v, Dh i ( x) = 0

T x

S

n p

h S

f : Ω R n R h( x) = 0 x S = x Ω : h( x) = 0 r > 0

y B( x , r) S f ( y) f ( x )

B( x , r)

f S x f ( x )

f

h( x) = 0 L( x, λ) ( x, λ) = (x 1 , × R p

λ p )

,

x n , λ 1 ,

,

L( x, λ) = f( x) + λ 1 h 1 ( x) + ··· + λ p h p ( x) = f( x) + λ, h( x) R.

x

f ( x) h( x) = 0

λ = (λ 1 ,

, λ p ) R p

DL x , λ

=

0.

λ

1 , x

, λ

p

x

λ R p ( x , λ ) L

S(f | h( x) = 0)

f : Ω R n R C 2

S

0 x f ( x) h( x) = 0

h : Ω R p C 2

= x Ω :

h( x) =

0

x

S

f

.

h( x) =

x ∈ S(f| h( x) = 0)

DL( x , λ ) = 0.

λ R p

x

f h C 2

h

H = D

2

x x

L( x , λ ) =

2

L

i x j ( x , λ

∂x

) i,j=1,

,n

M n (R)

L x ( x , λ ) q H ( u) =

u H t u

S = { x : h( x) = 0}

T x

S S x

q H T x S x f h( x) = 0

q H T x S x f h( x) = 0

0 q H T x S x f f h( x) = 0

H L x ( x , λ )

q H T x S